DYNAMICS OF SOCIAL ADAPTATION OF MIGRANT STUDENTS - Julian Amriwijaya; Sodjakusumah, Tutty I (International Journal of Teaching and Learning, 2024)
The dynamics of social adaptation of the migrants's students involve a series of complex and often changing processes over time. Social adaptation is the process in which individuals, groups, or social units adapt to the norms, changes, or conditions in their social environment. The process of social adaptation of regional students, or students studying away from their home, is influenced by various factors that can be inhibitory or supportive such as cultural differences and languages, lack of connection with local communities, attitudes that are difficult to accept change, and fear of cultural disintegration. This process is also affected by social support, tranquility, increased self-esteem, competence in social interaction, and cross-cultural communication skills. Cultural differences, social norms and different values can also trigger a culture shock in students who adapt to their new environment. The dynamics of social adaptation of students in the migrant involve continuous change and learning processes that can be very different for each individual. Students need to be flexible, proactive, and open to new experiences to meet the challenges and take advantage of the opportunities that exist in their new environment. In the context of social adaptation of regional students, it is important to understand the dynamics of their lives, the challenges facing them, as well as the efforts that can be made to facilitate the process of better social adaption.